2020
DOI: 10.1002/hep.31036
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Withdrawal in Liver Transplant Recipients on Sirolimus

Abstract: BACKGROUND AND AIMS As conversion from calcineurin inhibitor to sirolimus (SRL), a mechanistic target of rapamycin inhibitor (mTOR‐I), has been shown to enhance immunoregulatory profiles in liver transplant (LT) recipients (LTRs), mTOR‐I therapy might allow for increased success of immunosuppression (IS) withdrawal. Our aim was to determine if operational tolerance could be observed in LTRs withdrawn from SRL and if blood/graft tolerance biomarkers were predictive of successful withdrawal. APPROACH AND RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 47 publications
2
92
0
Order By: Relevance
“…Pittsburgh group reported that the increase in the ratio of plasmacytoid DCs to monocytoid DCs in peripheral blood was associated with successful withdrawal ( 90 ). Consistent with this finding, a study with a mammalian target of rapamycin (mTOR) inhibitor showed a higher proportion of tolerogenic DCs in tolerant recipients ( 74 ). An increasing number of regulatory T cell subsets (Tregs and gamma-delta T cells) and NK cells in peripheral blood are associated with tolerant recipients, which is consistent with their gene signatures ( 58 , 65 , 74 , 91 ).…”
Section: Immune Monitoring To Personalize Immunosuppression Toward Tomentioning
confidence: 60%
See 2 more Smart Citations
“…Pittsburgh group reported that the increase in the ratio of plasmacytoid DCs to monocytoid DCs in peripheral blood was associated with successful withdrawal ( 90 ). Consistent with this finding, a study with a mammalian target of rapamycin (mTOR) inhibitor showed a higher proportion of tolerogenic DCs in tolerant recipients ( 74 ). An increasing number of regulatory T cell subsets (Tregs and gamma-delta T cells) and NK cells in peripheral blood are associated with tolerant recipients, which is consistent with their gene signatures ( 58 , 65 , 74 , 91 ).…”
Section: Immune Monitoring To Personalize Immunosuppression Toward Tomentioning
confidence: 60%
“…Consistent with this finding, a study with a mammalian target of rapamycin (mTOR) inhibitor showed a higher proportion of tolerogenic DCs in tolerant recipients ( 74 ). An increasing number of regulatory T cell subsets (Tregs and gamma-delta T cells) and NK cells in peripheral blood are associated with tolerant recipients, which is consistent with their gene signatures ( 58 , 65 , 74 , 91 ). A recent report has shown the kinetics of increasing Tregs/Th17 cell ratio over the clinical course as a predictor of the development of tolerance ( 92 ).…”
Section: Immune Monitoring To Personalize Immunosuppression Toward Tomentioning
confidence: 60%
See 1 more Smart Citation
“…After 12 months from sirolimus withdraw, it showed that 8 recipients (53%) achieved OT. Of the other 7 patients, 3 failed IS withdrawal, 3 developed moderate cellular rejection (TCMR) on liver biopsies at the end of the study, and 1 was withdrawn from the trial owing to adrenal metastasis of hepatocellular carcinoma ( 32 ). The current result showed the OT rate of sirolimus was comparable to CNI-withdrawal studies.…”
Section: Current State In Spontaneous Tolerancementioning
confidence: 99%
“…Levitsky et al also found that, compared with the baseline, the tolerogenic dendritic cells (tolDC), regulatory B cells (Breg), and cell phenotypes associated with chronic antigen presentation in peripheral blood of the OT group was significantly higher than that of the non-OT group. In addition, gene signatures in peripheral blood/biopsy tissue showed that 12/14 LTR could accurately predict tolerance ( 32 ). Chruscinski et al performed a clinical trial (NCT02541916) for the predictive value of gene signatures in peripheral blood/biopsy tissue.…”
Section: Current State In Spontaneous Tolerancementioning
confidence: 99%